2017
DOI: 10.3758/s13421-017-0753-9
|View full text |Cite
|
Sign up to set email alerts
|

No advantage for remembering horizontal over vertical spatial locations learned from a single viewpoint

Abstract: Previous behavioral and neurophysiological research has shown better memory for horizontal than for vertical locations. In these studies, participants navigated toward these locations. In the present study we investigated whether the orientation of the spatial plane per se was responsible for this difference. We thus had participants learn locations visually from a single perspective and retrieve them from multiple viewpoints. In three experiments, participants studied colored tags on a horizontally or vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…This horizontal advantage is in line with the findings in multi-floor buildings. However, studies on memory for spatial locations in open spaces reported isotropic representations (Hinterecker et al 2018 ; Kim et al 2017 ). How could this discrepancy be explained?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This horizontal advantage is in line with the findings in multi-floor buildings. However, studies on memory for spatial locations in open spaces reported isotropic representations (Hinterecker et al 2018 ; Kim et al 2017 ). How could this discrepancy be explained?…”
Section: Discussionmentioning
confidence: 99%
“…First, neither Hinterecker et al ( 2018 ) nor Kim et al ( 2017 ) had participants encode the spatial information via real physical self-movement. Hinterecker et al ( 2018 ), had participants learn a spatial layout visually and without any locomotion. Kim and colleagues used visual motion in a virtual reality setup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu and Ye's wayfinding study (2017), in agreement with Berthoz & Thibault (2013;Thibault, et al, 2013), suggested that in multi-level buildings, people can integrate volumetric cognitive map and that the previous findings might be limited by the specific wayfinding task protocol used. To contribute to this debate meaningfully (Hinterecker, et al, 2018;Grieves, et al, 2020) and b. 3D medial center path encoding and 3D angular analysis principle (Cooper & Chiaradia, 2020).…”
Section: Geometry Scale and Metrical Considerations Line Of Movement ...mentioning
confidence: 99%